Investigating the Performance of a Few-Mode Fiber for Distributed Acoustic Sensing - Yuan Mao; Islam Ashry; Mohd Sharizal Alias; Tien Khee Ng; Frode Hveding; Muhammad Arsalan; Boon Siew Ooi (IEEE Photonics Journal, 2019)
We experimentally investigated the performance of a distributed acoustic sensor (DAS) designed using a few-mode fiber (FMF), when launching different spatial modes under intentional index perturbation within the fiber. Our demonstration showed that the quasi-single mode (QSM) operated FMF offers higher signal-to-noise ratio (SNR) for the DAS, compared with the case when launching other degenerate higher order modes. Additionally, we compared the behavior of the single-mode fiber (SMF)- and FMF-based DAS when using optical pulses of varying power levels. The FMF enables the realization of a DAS with longer sensing range and higher spatial resolution. The developed FMF-based DAS is further tested via sensing various vibration events produced by piezoelectric transducer (PZT) cylinder, pencil break, and loudspeaker.